A mixed endocrine adrenal tumour causing steatorrhoea. Issue 10 (October 1987) - Thesleff, P; Benoni, C; Mårtensson, H; Nilsson, A; Sundler, F; Akesson, B
Abstract : A 60 year old man developed steatorrhoea, weight loss, mild diabetes mellitus, labile hypertension and limb cramps. Raised plasma concentrations of catecholamines, particularly noradrenaline and a computed tomography-scan showing an adrenal tumour strongly suggested a pheochromocytoma. Adrenoreceptor blockade reversed the symptoms, decreased faecal fat, and increased duodenal trypsin to normal concentrations. After adrenalectomy the patient was asymptomatic and there was no steatorrhoea. The blood glucose concentrations became normal. Immunocytochemistry revealed the tumour cells to store large amounts of enkephalin and somatostatin reactive material and moderate amounts of immunoreactive beta-endorphin and dynorphin.